THE ROLE OF MARKETING RESEARCH IN IMPROVING THE EFFICIENCY OF HOTEL ENTERPRISES IN KAZAKHSTAN - Asan Zheldibayev; Yerkin Nessipbekov; Almaz Belgibayev; Zhanat Belgibayeva; Gulmira Appakova (Academic Journal of Physical and Chemical Sciences, 2020)
This article justifies the need for marketing research and provides an analysis of the situation in the hotel services market. When carrying out research the following methods were used: scientific abstraction, statistics-economical, analysis and synthesis. The following results were obtained in the course of scientific research: firstly, the role and importance of marketing research were considered; secondly, the analysis of Kazakhstan accommodation places by categories and visitors was conducted; thirdly, the prospects for the development of hotel business in Kazakhstan were justified.